(untitled) (Malay Literature, 2014)
A study of the connection between the literature of three areas (Singapore, Johor and Riau) was begun in 1987. The spirit and vision of these three areas was followed up with activities that accelerated the regional development of language, literature and culture. Dialog Selatan (Southern Dialogue) and meetings of scholars and intellectuals were among initiatives undertaken to reach a common goal towards preservation. What is the hope and aspiration behind these literary activities? This article explores initiatives taken and challenges faced by the three areas in preserving their literary ties throughout the 1990s. This article also introduces the efforts made to collect manuscripts and artifacts of Riau literature in Singapore, with the hope that it will open up ways for continued efforts towards the culture of research on materials in literature. Keywords: Southern Dialogue, Riau, Singapore